Did we overestimate the role of social preferences? The case of self-selected student samples - Armin Falk; Stephan Meier; Christian Zehnder (Institute for the Study of Labor (IZA), 2011)
Social preference research has received considerable attention among economists in recent years. However, the empirical foundation of social preferences is largely based on laboratory experiments with self-selected students as participants. This is potentially problematic as students participating in experiments may behave systematically different than non-participating students or non-students. In this paper we empirically investigate whether laboratory experiments with student samples misrepresent the importance of social preferences. Our first study shows that students who exhibit stronger prosocial inclinations in an unrelated field donation are not more likely to participate in experiments. This suggests that self-selection of more prosocial students into experiments is not a major issue. Our second study compares behavior of students and the general population in a trust experiment. We find very similar behavioral patterns for the two groups. If anything, the level of reciprocation seems higher among non-students suggesting that results from student samples might be seen as a lower bound for the importance of prosocial behavior.
urn:nbn:de:101:1-201104113482
Keywords: C90; D03; 330; methodology; selection; experiments; prosocial behavior; Soziale Wohlfahrtsfunktion; Austauschtheorie (Soziologie); Experimentelle Ökonomik; Studierende; Wissenschaftliche Methode; Vertrauen; Test